Constitutive overexpression of periostin delays wound healing in mouse skin. Issue 1 (7th March 2018) - Nunomura, Satoshi; Nanri, Yasuhiro; Ogawa, Masahiro; Arima, Kazuhiko; Mitamura, Yasutaka; Yoshihara, Tomohito; Hasuwa, Hidetoshi; Conway, Simon J.; Izuhara, Kenji
Abstract: Periostin is a matricellular protein involved in development, maintenance, and regulation of tissues and organs via by binding to cell surface integrin receptors. Pathologically, periostin plays an important role in the process of wound healing: as a deficiency of the Postn gene delays wound closure and periostin is consistently up‐regulated in response to injury and skin diseases. However, the functional role of elevated periostin in the process of wound healing has not been tested. In this study, we generated Postn ‐transgenic mice under the control of the CAG promoter/enhancer to investigate the effects of constitutive overexpression of full length periostin during its pathophysiological roles. Transgenic mice showed significant overexpression of periostin in skin, lung, and heart, but no morphological changes were observed. However, when these transgenic mice were injured, periostin overexpression delayed the closure of excisional wounds. Expression of IL‐1β and TNFα, pro‐inflammatory cytokines important for wound healing, was significantly decreased in the transgenic mice, prior to delayed healing. Infiltration of neutrophils and macrophages, the main sources of IL‐1β and TNFα, was also down‐regulated in the transgenic wound sites. From these data, we conclude that enforced expression of periostin delays wound closure due to reduced infiltration of neutrophils and macrophages followed by down‐regulation of IL‐1β and TNFα expression. This suggests that regulated spatiotemporal expression of periostin is important for efficient wound healing and that constitutive periostin overexpression interrupts the normal process of wound closure.